ANALISIS BIBLIOMETRIK AUDIT SUMBER DAYA MANUSIA MENGGUNAKAN VOSVIEWER DENGAN PUBLISH OR PERISH (POP) - Junillah Erdianti; Putri Wulandari; Laurencia Zennita; Dara Kesumadewi; Siti Rodiah (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
Human resource management is an important theme for the growth of organizations and companies, and many issues related to human resource management in order to maintain the smooth operation of the organization. The main objective of this study is to integrate mapping analysis techniques and the use of VOSviewer software to conduct a comprehensive bibliographic analysis of scientific literature related to human resource management audits. The research data were obtained using the Publish or Perish (PoP) application. The data collected were obtained from search results containing the keyword "human resource management audit" obtained from academic journals indexed by Google Scholar. This study identified a total of 500 papers from 2002 to 2024. The results showed that the number of studies conducted between 2002 and 2024 continued to increase. This study shows the importance of bibliographic analysis in providing analytical data on events. This study provides guidance and serves as a valuable resource for researchers who want to explore and identify research topics.